The Role of Soviet Propaganda Constructed "Soviet Hero" and its Dispersion in Eastem Europe. Rec.: Silke Satjukow, Reiner Gries. Sozialistische Helden. Eine Kulturgeschichte von Propagandafiguren in Osteuropa und der DDR. Berlin, 2002 - Žilvinas Kačiuška (Lietuvos Istorijos Studijos)
-